Globalization, Internationalization and Policy Networks in the U.S. - Wilson, Graham K. (My University, 2000)
Scholars should pay more attention to how world events affect politics in the United States, especially with increasing globalization and internationalization. This paper looks at how globalization and internationalization can affect U.S. policy networks -- the people, interest groups and institutions that interact when making public policy.